2022
DOI: 10.1101/2022.06.01.494304
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development of neonatal brain functional centrality and alterations associated with preterm birth

Abstract: Formation of the functional connectome in early life underpins future learning and behaviour. However, our understanding of how the functional organisation of brain regions into interconnected hubs (centrality) matures in the early postnatal period is limited, especially in response to factors associated with adverse neurodevelopmental outcomes such as preterm birth. We characterised voxel-wise functional centrality (weighted degree) in 366 neonates from the Developing Human Connectome Project. We tested the h… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Research in term-born neonates using this metric has found the most connected ("hub") regions in infancy to be in motor and primary sensory cortices (Fransson et al, 2011). While strength and heterogeneity of functional connectivity increases with age in most networks during infancy (Cao et al, 2017), recent work in predominantly term-born neonates of the dHCP cohort has highlighted that sensorimotor cortex shows a decrease in relative degree centrality with increasing postmenstrual age (Fenn-Moltu et al, 2022). This may reflect a normative fine-tuning in the regional specificity of sensorimotor connectivity with increasing exposure to the surrounding environment, consistent with the emergence of functional specialisation of network connectivity in this period (Cao et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research in term-born neonates using this metric has found the most connected ("hub") regions in infancy to be in motor and primary sensory cortices (Fransson et al, 2011). While strength and heterogeneity of functional connectivity increases with age in most networks during infancy (Cao et al, 2017), recent work in predominantly term-born neonates of the dHCP cohort has highlighted that sensorimotor cortex shows a decrease in relative degree centrality with increasing postmenstrual age (Fenn-Moltu et al, 2022). This may reflect a normative fine-tuning in the regional specificity of sensorimotor connectivity with increasing exposure to the surrounding environment, consistent with the emergence of functional specialisation of network connectivity in this period (Cao et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In order to derive voxelwise degree centrality maps (Fenn-Moltu et al, 2022), the timeseries from each voxel within the cortical grey matter mask (in template space) were extracted and a correlation matrix constructed from pairwise Pearson correlations between each pair of voxels. Correlations below 0.20 were excluded in order to avoid including spurious connections likely caused by noise.…”
Section: Functional Data Pre-processingmentioning
confidence: 99%
“…Resting-state functional MRI (rs-fMRI) data were pre-processed as in our previous work ( 50 ); for more details see Supplemental Information. Functional connectivity was evaluated using a measure of weighted degree centrality at the voxel-level (i.e., the sum of the correlations between the time-series of each voxel and all other voxels within a grey matter mask of the brain) ( 51,52 ). Edges with a correlation coefficient below a threshold of 0.2 were excluded and the degree centrality values for each voxel in the grey matter mask were z-scored and used in subsequent between-subgroup analyses.…”
Section: Methodsmentioning
confidence: 99%